Meningkatkan Aktivitas Dan Hasil Belajar Siswa Menggunakan Model Pemberi Pada Siswa Kelas III - Noorhapizah; Rusmini (CV. ITTC INDONESIA, 2023)
The desired condition in learning is that students are actively and actively involved in the learning process and there is an increase in student learning outcomes. However, the reality on the ground shows that these ideal conditions have not been realized. Therefore, the researchers took the initiative to apply the PEMBERI approach and learning model that focused on students. This study aims to describe how the PEMBERI model can increase student activity and achievement. This research used a qualitative approach with a class action research type that was held in four meetings. The research location was conducted in class III SD Negeri Kelayan Timur 9 Banjarmasin. The information utilized in this study encompasses qualitative and quantitative data. Qualitative data were acquired by observing student engagements, whereas quantitative data were gathered via individual assessment examinations. Data analysis was performed using descriptive analysis and cross tabulation analysis. The findings from this study indicate a significant increase in student activity and achievement.